Color works : best practices for graphic designers : an essential guide to understanding and applying color design principles - Opara, Eddie, 1972- (Rockport Publishers, 2014)
"This is the go-to guide for designers as it outlines and details the essential color design skills needed to create successful, meaningful, and aesthetically compelling designs. Along with hands-on projects, it offers unique insights into strategy and business when working in the real world with real clients. Color Works starts with basic information on color practices and fundamentals, and then delves more deeply into theory and application on a project-by-project basis. Illustrated with real-world projects and case studies, this book offers a behind-the-scenes take on the design process and the necessary steps to go from concept to final outcome, including the challenges encountered along the way"--